Hegemony and Representation of Black Actresses in The Little Mermaid (2023) - OK Dedi Arwansyah; Muhammad Rasyad Ghazali Saraan; Armansyah Matondang; Eka Fatmawati (Mahesa Research Center, 2025)
This article reviews the debate and impact of Halle Bailey's selection as Ariel in the live-action film